What Mathematical Images Are in a Typical Mathematics Textbook? Implications for Students with Visual Impairments. (January 2018) - Emerson, Robert Wall; Anderson, Dawn
Introduction: Visually impaired students (that is, those who are blind or have low vision) have difficulty accessing curricular material in mathematical textbooks because many mathematics texts have visual images that contain important content information that are not transcribed or described in digital versions of the texts. However, little is known about the extent to which this issue exists within texts and what sort of information is contained in visual material in mathematics texts. This article describes a process undertaken to classify images in a selection of math textbooks that are currently being used in grades 5, 8, and 11. Methods: Representative textbooks were chosen that aligned with Common Core Standards. An exhaustive and mutually exclusive set of image categories was developed, researchers became reliable on coding procedures, and then all images in the representative texts were coded. Results: The most common images involved student interest, motivation, and organization, but contained little or no math content. The second most common area of image categories often contained large amounts of math content but were difficult to describe succinctly or might have been described without including important mathematical information. This grouping included tables, line graphs, and images specifically related to a single question. The final group of less frequently appearing images included ray or line diagrams, number lines, pie charts, bar graphs, and maps. Discussion: To improve access to visual math content, the focus should be on images that appear frequently and contain math content such as tables, scatter or line graphs, shapes, equations, and images specifically related to a single question. Less common image categories such as models, line diagrams, pictures of calculator keys, and number lines lend themselves easily to description. Implications for practitioners: Optimization of limited instructional time would be accomplished by having teachers focus on students' understanding of the most common types of images, such as tables and line graphs.